Construction and development of quantitative scale to measure source credibility in the maternal mortality context - Mustaffa, Che Su; Abdul Baqi, Saudat (Universiti Putra Malaysia Press, 2016)
Many communication studies have established the role of credibility of the source on effective information dissemination. In particular, the factors of believability, trustworthiness, and related attitudinal attributes of the source have been found to have a high influence on the effectiveness of a message. However, very little attention has been paid to the influence of the demographic characteristics of the source. The major objective of this study was to develop a scale for measuring characteristics of gender, age, and socio-economic status of the source on effective dissemination of information on maternal mortality. The inclusion of factors such as perceptions of gender, age and socio-economic status of the source to source credibility study provides a sound appreciation of the influence of visible characteristics of the source on attitudinal and behavioral changes on the content of disseminated messages. Accepted psycho metrics scale-development procedures were followed that rigorously tested a large pool of items for their reliability and validity.A total of 365 respondents were involved in this study. Data for the study were gathered through quantitative surveys that included men, and women of childbearing age in north-central Nigeria. Using exploratory and confirmatory samples, the current research developed a 16-item semantic differential scale to measure the influence of demographic characteristics of the source on effectiveness of delivering a message. The scale was validated using respondents’ self-reported measures perception toward the source’s gender, age and socio economic status. From a theoretical perspective, by identifying and measuring this tricomponent construct, the researcher can validly assess the impact of each of the dimensions on the source credibility scale on maternal mortality information.The findings of this research have supported the views of previous scholars that the effectiveness of disseminated information depends largely on the credibility of the source. The resulting scale demonstrated high reliability and validity.The generated instrument has increased the array of measuring items that are available for source credibility and diffusion of innovation studies. The acceptable validity and reliability values of the instrument strengthen their replication in other studies and other context.The findings of this study contribute to knowledge both at the academic and pragmatic realms.They offer important contributions for communication planners change agents and individuals in their day-to-day communication discourse on the application of source credibility and diffusion of innovation theories.Consistent with source credibility theory-based studies, this study has justified the assertion that an increased perception of characteristics of the source leads to an increase in message effectiveness as proved by the introduction of demographic features of the source to the source credibility model.Findings are explained in depth and methodological, theoretical and managerial implications are highlighted.